Interstitial water of deep, stratified lake as potential source of internal phosphorus loading – implications for preventing eutrophication - Łopata, Michał; Tandyrak, Renata; Augustyniak, Renata; Parszuto, Katarzyna; Płachta, Anna; Cybulska, Zuzanna (Lviv Politechnic Publishing House, 2019)
The paper evaluates the potential impact of internal biogenic pollutants (phosphorus) on the trophic state of the deep, stratified Lake Swiete in Obra, Poland (area 23.3 ha, depth 15.3 m). The amount of phosphorus in interstitial water was analyzed on the basis of spatial studies of 10 cm of surface sediments of bottom sediments. It has been shown that the release of loading accumulated in the water can worsen the trophic state of the lake.
Keywords: bottom sediments; eutrophication; internal loading; interstitial water; phosphorus